Access to higher education and inequality: the Chinese experiment - Xiaojun Wang; Belton M. Fleisher; Haizheng Li; Shi Li (Institute for the Study of Labor (IZA), 2007)
We apply a semi-parametric latent variable model to estimate selection and sorting effects on the evolution of private returns to schooling for college graduates during China's reform between 1988 and 2002. We find that there were substantial sorting gains under the traditional system, but they have decreased drastically and become negligible in the most recent data. We take this as evidence of growing influence of private financial constraints on decisions to attend college as tuition costs have risen and the relative importance of government subsidies has declined. The main policy implication of our results is that labor and education reform without concomitant capital market reform and government support for the financially disadvantaged exacerbates increases in inequality inherent in elimination of the traditional wage-grid.
urn:nbn:de:101:1-20080328111
Keywords: 330; Bildungschancen; Bildungsertrag; Soziale Ungleichheit; Bildungsreform; China